Peningkatan Pengetahuan Ergonomi Tentang Prinsip Prinsip Dalam Gerakan Di Sekolah SMAN 2 Bireuen - Muhammad Zia Ulhaq; Imam Muhammad Amhar; Nurul Husna; Alfi Syahrin; Al Iqlima; Siti Mukarramah; Melindawati Melindawati; Safrida Safrida; Maria Ulfa (Universitas 45 Surabaya, 2024)
The purpose of this socialization is to find out about increasing knowledge of ergonomics and the principles of movement at SMA N 2 Bireuen. The results of this activity with socialization and discussion can increase students' understanding of ergonomics and its principles. Increasing understanding of the ergonomics of ergonomic sitting positions among students at SMA N 2 Bireuen will help reduce the risk of physiological and ergonomic complaints, as well as improve academic performance at school. It is hoped that the school will carry out this movement regarding ergonomics.